Некоторые морфологические и биохимические показатели крови карпов и сазано-карпопых гибридов при инвазии паразитами - Возный, Н.Е.; Ивасик, В.М. (Вестник зоологии, 1974)
Infestation of the two-year carps and common carp-carp hybrids with Sphaerospora carassii and the helminths - Dactylogyrus extensus, Khawia sinensis, Bothriocephalus gowkongensis evokes changes in the morphological composition of blood and protein picture of its serum. In fishes infected with Sphaerospora carassii and in mixed invasion with Sph. caarssii and the above-mentioned helminths more serious changes are observed than in those infected only with the helminths. The changes in blood are more significant in carps than in common carp-carp hybrids.